THE AWARENESS OF ICT USE FOR TEACHING AND LEARNING PROCESS EFFECTIVELY - ASTI GUMARTIFA (Sriwijaya University Learning and Education International Conference, 2016)
Information, Communication, and Technologies (ICT) are always influence allaspects of life. The use of ICT has an importance role in work places, business,entertainment, moreover in education. It is as a certain thing which is needed due tosupport teaching and learning process. ICT can also create student-centered learningsetting to be more active and creative. Besides, ICT can also develop the quality,accessibility, and learning motivation in education. Therefore, teachers have a verybig role due to know how to integrate the technology into classroom practices. Thispaper discusses the importance of ICT use, benefits of ICT use, and barriersintegration of ICT use in the class-room practiced. Therefore, the main purpose ofthis study is to develop teachers’ and students’ awareness of ICT integration due toachieve successful learning.